1994
DOI: 10.1007/bf00191716
|View full text |Cite
|
Sign up to set email alerts
|

Neurohormone D induces ionic current changes in cockroach central neurones

Abstract: The octapeptide neurohormone D (NHD), a member of the family of adipokinetic hormones (AKH-peptides), increases the frequency of spontaneous activity in dorsal unpaired median (DUM) neurones isolated from the terminal ganglion of the cockroach Periplaneta americana. The increase in spike frequency is accompanied by changes in the shape and the amplitude of the single action potentials, e.g. a more pronounced afterhyperpolarization. Effects of NHD on membrane currents were investigated in these DUM cells with w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
35
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 37 publications
4
35
0
Order By: Relevance
“…Cell Isolation-Isolation of adult DUM neuron cell bodies was performed under sterile conditions using enzymatic digestion and mechanical dissociation of the median parts of both fifth and terminal abdominal ganglia of adult male cockroaches (Periplaneta americana), as described previously (8,11). Briefly, ganglia were excised, desheathed, and incubated for 10 min at room temperature in bath solution (BS1) containing (in mM): 190 NaCl, 5 KCl, 5 CaCl 2 , 2 MgCl 2 , 10 HEPES, pH 7.4) containing 0.5 mg/ml trypsin (type II, Sigma) and 0.5 mg/ml collagenase (type I, Sigma).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell Isolation-Isolation of adult DUM neuron cell bodies was performed under sterile conditions using enzymatic digestion and mechanical dissociation of the median parts of both fifth and terminal abdominal ganglia of adult male cockroaches (Periplaneta americana), as described previously (8,11). Briefly, ganglia were excised, desheathed, and incubated for 10 min at room temperature in bath solution (BS1) containing (in mM): 190 NaCl, 5 KCl, 5 CaCl 2 , 2 MgCl 2 , 10 HEPES, pH 7.4) containing 0.5 mg/ml trypsin (type II, Sigma) and 0.5 mg/ml collagenase (type I, Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…The latter can be blocked by cadmium (8), NPPB, and mefenamic acid (9). This current seems to be physiologically important for: 1) adjusting the free intracellular calcium concentration ([Ca 2ϩ ] i ) (9), and 2) filling intracellular calcium stores (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While the lower dose of applied AKHs had stimulatory effects on walking activity of macropterous females of P. apterus, higher doses of these hormones showed no or even slightly inhibitory effects on the locomotion of this bug, despite their positive effects on the mobilization of lipids. The presumption that AKH might play an important role as a neuromodulator is supported by findings that CC extracts, neurohormone D, and AKH can exhibit, in a manner similar to octopamine, a strong modulatory effect on the CNS of some insects (Milburn & Roeder, 1962;Milde et al, 1995;Wicher et al, 1994). In addition, the presence of AKH in CNS neurones (Schooneveld et al, 1985) or even in axons was demonstrated by immunohistochemistry, but, as mentioned earlier, a direct explanation of its physiological role is not yet available.…”
Section: Adipokinetic Activity Of Peram-cah-ii and Panbo-rcph In P Amentioning
confidence: 66%
“…Previous investigations on identified insect neurosecretory neurons, namely efferent dorsal unpaired median (DUM) neurons in the cockroach Periplaneta americana, have shown that a voltage-independent Ca 2ϩ background current providing for non-capacitative Ca 2ϩ entry (NCCE) changes the spike frequency of these cells. For example, up-regulation of this current by the Periplaneta adipokinetic hormone AKH I (pAKH I: pQ-V-N-F-S-P-N-W⅐NH 2 , also named neurohormone D (6)), accelerates spiking (7,8). A detailed analysis of the signal transduction mechanism, by which AKH I binding to the receptor leads to potentiation of Ca 2ϩ background current, revealed a complex pattern of events including activation of PLC but no apparent contribution from intracellular Ca 2ϩ stores (8).…”
mentioning
confidence: 99%